Unicorns aren't a fairytale, China is their Valley (2019)
The purpose of this article is to present an overview of the Chinese cities where unicorn companies proliferate, as well as the sectors in which they concentrate. Unicorn companies are newly created private companies with a valuation of more than one billion US dollars. In 2018 there are 260 unicorn companies worldwide, 76 are located in China, while the United States of America has 121, a front where the commercial war between the two world super powers is also fought. China has made remarkable progress in this matter. In 2009 there were only two Chinese unicorns, now China's unicorn companies represent almost 30% of the total in the world. Between 2017 and 2018, 16 new unicorns have emerged.